(untitled) (Eurasian Journal of Ecology, 2016)
Known methods of an economic assessment of natural resources, ecosystem services, ecological extremeness in a context of the principles of "green" economy are considered. Aspects of criticism of gross domestic product as inefficient indicator reflecting ekologo-economic factors, level of insufficient financing and subsidizing of "green" sectors are analyzed. Calculations of an assessment of natural resources (mineral raw materials, land, water resources) Kazakhstan are given.